Дослідження ресурсу роботи спинки ножа сегментно-пальцевого різального апарату - Бабій, М. В.; Попович, П. В.; Матвіїшин, А. Й.; Бабій, А. В.; Babiy, Maria; Popovich, Pavlo; Matviyishyn, Anatoly; Babiy, Andriy (КНТУ, 2015)
В роботі проведено розрахунок ресурсу роботи спинки ножа косарки сегментно-пальцевої, встановлено його відповідність до нормативу. За результатами аналізу роботи приводного механізму запропоновано додатковий пристрій для зменшення негативного впливу інерційних знакозмінних сил на різальний апарат косарки та елементи його приводу. Отриманий ефект значно підвищує ресурс роботи спинки ножа.The objective of investigation is to calculate real blade-back service life basing on the carried out theoretical and experimental investigations of the segment-pin cutting unit mower with crank drive taking advantage of the device for reducing dynamic forces. The calculation of the segment-pin mower blade-back service life has been carried out and its correspondence to the standard was determined. According to the analysis of the drive mechanism operation additional device for reducing of the disadvantageous affect of inertia alternating forces on mower cutting device and its drive elements has been proposed. The obtained result increases the blade-back service life sufficiently. The advantage of our investigation is that application of power-saving drive mechanism makes possible not only to save energy consumed by the mower drive, but to increase the service life of important part of the cutting device–blade back.
Investigation of the blade-back service life of the segment-pin cutting device
Keywords: привод; різальний апарат; концентратор; циклічна втома; ресурс роботи; drive; cutting device; concentrator; cyclic fatigue; service life